Monitoring the agri-food system in Myanmar: The rising costs of diets and declining purchasing power of casual wage laborers: June 2020 - February 2023 - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
We assess changes in food prices and purchasing power of casual wage laborers based on large-scale surveys of food vendors (fielded from June 2020 until February 2023) and households in rural and urban areas and in all state/regions of Myanmar. Key findings  Over the full period (June 2020 - February 2023), the cost of the healthy diet rose by 72 percent and the common diet by 82 percent.  Prices for rice –the major staple– increased by 62 percent between March 2022 and February 2023.  The costs of a common and healthy diet increased especially over the year 2022, by 50 and 51 percent respectively between Q1 of 2022 and Q4 of 2022.  Diet costs increased more in rural areas compared to urban areas and more in the Dry Zone and coastal areas – which are more affected by conflicts – compared to the national average.  The value of daily wages of construction and agricultural wage laborers relative to common and healthy diet costs declined by about 25 and 28 percent over the year 2022.  Food costs are outpacing wages, making food increasingly unaffordable for wage earners who are among the most vulnerable household groups in Myanmar, particularly in rural areas. Recommended actions  Food should be available at low costs to avoid food insecurity and nutrition problems in the country; assuring a well-functioning agri-food system should therefore be a priority for all stakeholders.  Casual wage workers are among the poorest and their situation is worsening. They should therefore be targeted in social safety net programs.  It is important to closely monitor food prices and the wages of the poor - they are good proxies for purchasing power and welfare and can be measured at high frequency.